Coleridge on drama - Wagstaff, Brian John (Rhodes University, Faculty of Humanities, Department of Literary Studies in English, 1973)
From Introduction: In the Preface to his book The idea of Coleridge's Criticism, Richard Harter Fogle states: There is... I am confident, a need for such a study as I here introduce; a study of Coleridge's criticism in itself, tentatively accepting the metaphysical assumptions on which it is based and focusing upon its central principles and inner relationship; endeavouring without direct regard for its external connections to the past and the present to see it as a whole, yet at the same time anxiously regardful of its permanent significance and its bearing upon practical criticism. These are the principles on which I have based this thesis, applied more particularly to Coleridge's criticism of drama.
Keywords: Coleridge, Samuel Taylor, 1772-1834 -- Dramatic works; Coleridge, Samuel Taylor, 1772-1834 -- Criticism and interpretation; English drama -- 18th century -- History and criticism